Soybean oil-based green diesel production via catalytic deoxygenation (CDO) technology using low-cost modified dolomite and commercial zeolite-based catalyst - Hafriz, R.S.R.M.; Habib, S.H.; Raof, N.A.; Ong, M.Y.; Seah, C.C.; Razali, S.Z.; Yunus, R.; Razali, N.M.; Salmiaton, A. (Elsevier, 2024)
Green diesel derived from sustainable biomass is an alternative and potential energy source to petroleum fossil fuel replacement in response to reducing carbon footprint and achieving a circular economy, which has sparked public interest and concern in advancing renewable energy development. Catalytic deoxygenation (CDO) is a promising method because it can process a wide variety of feedstocks and produce a diverse range of fuels. The CDO of soybean oil (SO) was executed using a modified low-cost dolomite catalyst denoted as NiO-CD catalyst and its performance has been compared with commercial zeolite heterogeneous-based catalysts such as ZSM-5, HY-zeolite and FCC. The NiO-CD catalyst exhibited exceptional deoxygenation ability, attaining an 88.6 % removal efficiency of oxygenated compounds, markedly surpassing all commercially available zeolite catalysts. The highest degree of CDO of SO via decarboxylation/decarbonylation (deCOx) reaction was achieved due to improvement in particle size, mesoporous structure and the presence of the synergistic effect of modified bi-functional acid-base properties of NiO-CaO/MgO catalyst. To investigate the effect of NiO-CD catalyst loading ranging from 1 to 7 wt%, a One Factor At a Time (OFAT) optimisation study was performed. The current study found that an optimised NiO-CD catalyst loading of 5 wt% yielded the highest green diesel (50.5 wt%) with an 88.63 % hydrocarbon composition. The influence of catalyst loading on deoxygenation activity is significant in green diesel production using NiO-CD catalyst. © 2024